ANALISIS TINGKAT KEMAMPUAN PENGUSAHA UMK DALAM MENGAKSES KREDIT PERBANKAN SYARIAH DI KOTA MEDAN (STUDI KASUS : BANK SUMUT SYARIAH CABANG MEDAN) - Pra Vita Sari; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to analyze the capability rate of MSE entrepreneurs to access financing in Islamic banking in Medan, case study SUMUT Syariah Bank, Medan. This research using descriptive method with the primary data. The data collected through interviews and questionnaires. This study is conducted to know the reason, the potential and constraints of entrepreneurs in SMEs in accessing finance, especially Islamic banking at SUMUT Syariah Bank. Based on the results of the study indicate that the reason for MSE entrepreneurs access financing in Islamic banking because proposals from friends / family and MSEs entrepreneurs potential in accessing finance the initial capital and MSE entrepreneurs income and the constraints faced is the need to have a business license and financial statements each month.Keywords : Financing, MSE, Islamic Banking, Capability